ORC fluids selection for a bottoming binary geothermal power plant integrated with a CSP plant. (15th February 2023) - Boukelia, T.E.; Arslan, O.; Djimli, S.; Kabar, Y.
Abstract: Hybridization of geothermal power plants with concentrating solar power systems is an attractive solution to enhance the dispatch capacity of thermal power plants. Hence, the design and thermo-economic analyses of a combined solar-geothermal power plant with different organic fluids have been investigated. This configuration generates electricity at two temperature levels; high one at a topping parabolic trough solar power plant, and low one at a bottoming binary geothermal plant. The topping solar plant is equipped with energy storage and fuel backup systems simultaneously to maximize the generated power. Furthermore, the bottoming geothermal plant has been analyzed with nine different organic fluids. The obtained results show that power generation of this configuration has been raised by more than 19.36% at nominal conditions compared to the reference stand-alone solar plant. Moreover, organic fluids with wet behavior show better performances than those with dry one. In this regard, ammonia, R32, R290, and R143a are more efficient than the others, where annual net outputs of 22.20, 20.02, 19.25, and 18.67 GWhe have been produced, respectively. Furthermore, the combined plant with ammonia as the working fluid in the bottoming installation has the lowest levelized cost of electricity with a value of 10.42 ¢/kWh. Highlights: The design of a new PT-geothermal plant and its performances have been presented. The topping plant is based on a parabolic trough technology similar to Archimede. The bottoming plant is based on a binary geothermal power configuration. The techno-economic performances of the new plant are analyzed and compared to Archimede. Different organic fluids in the bottoming configuration are investigated.